2012
DOI: 10.1063/1.4742159
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing extreme ultraviolet photons emission in laser produced plasmas for advanced lithography

Abstract: Current challenges in the development of efficient laser produced plasma sources for the next generation extreme ultraviolet lithography (EUVL) are increasing EUV power and maximizing lifetime and therefore, reducing cost of devices. Mass-limited targets such as small tin droplets are considered among the best choices for cleaner operation of the optical system because of lower mass of atomic debris produced by the laser beam. The small diameter of droplets, however, decreases the conversion efficiency (CE) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…11 Similar values were predicted using our HEIGHTS simulations. 3 Variations in parameters of the CO 2 laser, i.e., increase of pulse intensity or spot size, do not significantly increase CE of such single pulse laser devices using small spherical targets. This is mainly due to the high reflection of 10.6-lm wavelength from solid/liquid tin, low critical density, and therefore lower vaporization of droplet by CO 2 laser, and less confinement of the evolved plasma plume to efficiently absorb and reabsorb (after reflection) laser photons due to the hydrodynamic motion of plasma around the droplet.…”
Section: Mist Creation From Dropletsmentioning
confidence: 95%
See 3 more Smart Citations
“…11 Similar values were predicted using our HEIGHTS simulations. 3 Variations in parameters of the CO 2 laser, i.e., increase of pulse intensity or spot size, do not significantly increase CE of such single pulse laser devices using small spherical targets. This is mainly due to the high reflection of 10.6-lm wavelength from solid/liquid tin, low critical density, and therefore lower vaporization of droplet by CO 2 laser, and less confinement of the evolved plasma plume to efficiently absorb and reabsorb (after reflection) laser photons due to the hydrodynamic motion of plasma around the droplet.…”
Section: Mist Creation From Dropletsmentioning
confidence: 95%
“…HEIGHTS Monte Carlo models for laser energy deposition take into account laser photons interaction with solid/liquid target, with vapor and plasma including photons absorption, reflection, and reabsorption after reflection. 3,6 Detailed model for target vaporization are based on target thermophysical properties as well as the kinetics of evaporation and takes into account possibility of recondensation. 8 The developed algorithms in HEIGHTS for unstructured mesh generation allow, for example, fine resolution of most important regions in domain, e.g., around 0.1 lm cell size for the target surface.…”
Section: Brief Description Of the Integrated Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] We evaluated using our HEIGHTS simulation package the CE of dual-beam systems with various droplet sizes, starting from 10 lm, and our results indicated that the smallest efficient droplets should be in the range of 20-30 lm. 7,8 The purpose of this study is to investigate the differences in EUV photons production for different geometries and target conditions that can explain recent experimental results and then demonstrate ways for future target optimizations in these regards. We also studied the influence of different processes on EUV source characteristics for various preplasma conditions and main laser parameters.…”
Section: Introductionmentioning
confidence: 99%